2017
DOI: 10.18632/oncotarget.15340
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of mucin glycoprotein MUC1 in the progression to esophageal adenocarcinoma and therapeutic potential with a targeted photoactive antibody-drug conjugate

Abstract: BackgroundMucin glycoprotein 1 (MUC1) is a glycosylated transmembrane protein on epithelial cells. We investigate MUC1 as a therapeutic target in Barrett’s epithelium (BE) and esophageal adenocarcinoma (EA) and provide proof of concept for a light based therapy targeting MUC1.RESULTSMUC1 was present in 21% and 30% of significantly enriched pathways comparing BE and EA to squamous epithelium respectively. MUC1 gene expression was x2.3 and x2.2 higher in BE (p=<0.001) and EA (p=0.03). MUC1 immunohistochemical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Generally, uPAR expression is higher at the invasive front of the tumor and lower at the core [21]. Reported IHC expression rates of CEA, EMA, and EpCAM are comparable to those in our results [22][23][24][25].…”
Section: Discussionsupporting
confidence: 89%
“…Generally, uPAR expression is higher at the invasive front of the tumor and lower at the core [21]. Reported IHC expression rates of CEA, EMA, and EpCAM are comparable to those in our results [22][23][24][25].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we suggested that MUC1 was highly expressed in recurrent LMS and LPS, suggesting a potential novel biomarker to predict STS recurrence. Additionally, as an extensively O-glycosylated and moderately N- glycosylated transmembrane protein on epithelial cells, many antibody-drug conjugates (ADC) have been explored for MUC1, such as HuHMFG1 [32, 33]. Thus, MUC1 can be regarded as a potential therapeutic target for recurrent STS.…”
Section: Discussionmentioning
confidence: 99%
“…Lovat et al reported the efficacy of the hHuHFMG1 ADC in esophageal adenocarcinoma. 33 Kufe et al reported an ADC targeting the non-glycosylated C-terminal of MUC1. 34 Antitumor efficacy and toxicity are two major criteria to be assessed for their clinical application.…”
Section: Discussionmentioning
confidence: 99%